My Unsentimental Education - Monroe, Debra (Book collections on Project MUSE., 2015)
"A misfit in Spooner, Wisconsin with its farms, bars, and strip joints, Debra Monroe leaves to earn a degree, then another, another, and builds a career--if only because her plans to be a Midwestern housewife continually get scuttled. Her professional life improves because she's good at 'hard-core feigning.' Fearless but naive, she vaults over class barriers, but never quite leaves her past behind. When it comes to men, she's still blue-collar. Monroe pays careful attention to what love and sex mean to a 'liberated' woman: to the pressure to be assertive yet not too assertive; to different prices women pay for being 'sultry-powerful' or 'brainy-powerful.' Both the story of her steady rise into the professional class and a parallel history of unsuitable exes, this memoir reminds us how accidental even a good life can be. If Joan Didion advises us 'to keep on nodding terms with the people we used to be, ' Monroe takes this advice a step further and nods at the people she might have become but didn't. Funny, poignant, wise, My Unsentimental Education explores the confusion that ensues when a working class girl ends up far from where she began"--Provided by publisher